The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/es103336s
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modeling for Groundwater Arsenic Levels in North Carolina

Abstract: To examine environmental and geologic determinants of arsenic in groundwater, detailed geologic data were integrated with well water arsenic concentration data and well construction data for 471 private wells in Orange County, NC, via a geographic information system. For the statistical analysis, the geologic units were simplified into four generalized categories based on rock type and interpreted mode of deposition/emplacement. The geologic transitions from rocks of a primary pyroclastic origin to rocks of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 45 publications
2
51
2
2
Order By: Relevance
“…The geocoding methods developed in this study data enabled a comprehensive report of over 4,000 yearly arsenic measurements with geographical coordinates from 1998-2007 and over 10,000 from 2008 to present, a substantial increase relative to the USGS and EPA ambient monitoring systems. Specifically, the number of records analyzed represents a 600-fold increase from samples collected by the USGS (USGS 2010) and more than three times the number of records analyzed in other studies North Carolina wells (Pippin 2005; Kim et al in press ). The substantial increase in recent well sampling is likely due to state legislation adopted in 2008 that requires every newly constructed well be tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The geocoding methods developed in this study data enabled a comprehensive report of over 4,000 yearly arsenic measurements with geographical coordinates from 1998-2007 and over 10,000 from 2008 to present, a substantial increase relative to the USGS and EPA ambient monitoring systems. Specifically, the number of records analyzed represents a 600-fold increase from samples collected by the USGS (USGS 2010) and more than three times the number of records analyzed in other studies North Carolina wells (Pippin 2005; Kim et al in press ). The substantial increase in recent well sampling is likely due to state legislation adopted in 2008 that requires every newly constructed well be tested.…”
Section: Discussionmentioning
confidence: 99%
“…We increased the knowledgebase using available locational information to assign geographic coordinates of domestic wells based on four spatial classes: GPS, street address, zip code, and county. As an example, we tripled the number of successfully geocoded points used in previous analyses over comparable geographic areas and timeframes (Pippin 2005; Kim et al in press ). Additionally, while others have shown that multi-stage geocoding methods improved the match rate compared to single-step methods (Lovasi et al 2007), to our knowledge, the present study is one of the first to use GPS locations to systematically quantify and account for geocoding location error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High arsenic (As) concentrations in domestic bedrock wells have emerged as a public health concern in Africa (Kortatsi, 2007; Smedley, 1996; Smedley et al, 2007), Asia (Ahn, 2012; Shukla et al, 2010), Europe (Aloupi et al, 2009; Heinrichs and Udluft, 1999), and Central and North America (Armienta et al, 2001; Ayotte et al, 2003; Boyle et al, 1998; Colman, 2011; Kim et al, 2011; Lipfert et al, 2006; Peters and Blum, 2003; Peters and Burkert, 2008; Pippin et al, 2006; Ryan et al, 2011; Yang et al, 2009), especially in rural areas without public water supply. These bedrock wells typically have low yields and supply small communities or individual households (Drew et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…이러한 GIS의 특징은 다양한 도 형자료와 속성자료를 가지고 있는 수많은 데이터 파일에서 필요한 도형이나 속성정보를 추 출하고 결합하여 복잡하고 종합적인 각종 정보를 분석⋅처리 할 수 있다는 것이다 (박노욱, 권병두, 2000). (김묘정, 최아현, 2008; 김호용, 김지숙, 이성호, 2012; 정건섭, 김성우, 이양원, 2012; 조성호, 박순호, 1996), 최적경로분석(양광식, 2011), 수배송관리 (김시곤, 김황배, 2002; 이희연, 임은선, 2001), 관광 루트분석 (오규식, 박경호, 1997), 응급의료 (김흥순, 정다운, 2010;이태식, 구지희, 1996;Kim et al, 2011;Kim, Galeano, Hull, & Miranda, 2008;Kim, Lauria, & Whittington, 2012), 재해 관리 (김지숙, 김호용, 이성호, 2014; 이사로, 김윤종, 민경덕, 2000), 정치 (박기호, 2000;Auchincloss et al, 2007;Hernández-Murillo, 2003;Sui & Hugill, 2002;Voss, Long, Hammer, & Friedman, 2006 …”
unclassified